KEPATUHAN PENYELENGGARA PELAYANAN PUBLIK DALAM PELAKSANAAN REKOMENDASI OMBUDSMAN REPUBLIK INDONESIA TERKAIT TINDAKAN MALADMINISTRASI TAHUN 2019 - Muhammad Fachry Dharmawan; Robinsar Marbun (Fakultas Hukum Universitas Tulang Bawang, 2020)
Public services are the key to running a perfect government in the framework of the obligation to serve its citizens. In practice, we often encounter complicated problems from the start to the end. So that this bureaucratic process becomes long, inefficient, and expensive. A fast and precise process is needed so that the public service process will be better in the future. One of the causes of not optimal public services in Indonesia is due to inadequate supervision of internal government. Finally, supervisory agencies have become important in their existence in Indonesia, both for direct investigation and following up on reports from the public. After conducting an investigation, the Ombudsman of the Republic of Indonesia will issue a recommendation if it is proven that the public service institution has committed maladministration. However, many question whether these recommendations are being followed. Then whether the recommendation is sufficient as a sanction for maladministration is still in question. This certainty is important to ensure that the government's performance remains prime and fully pro-people. Keywords : Public Services, Bureaucracy, Public Service Supervisory Agency, Maladministration